Involvement of the epidermal growth factor receptor in the modulation of multidrug resistance in human hepatocellular carcinoma cells in vitro - Hoffmann, Katrin; Xiao, Zhi; Franz, Clemens; Mohr, Elvira; Serba, Susanne; Büchler, Markus W.; Schemmer, Peter (Cancer cell international, 2011)
Hepatocellular carcinoma (HCC) is a molecular complex tumor with high intrinsic drug resistance. Recent evidence suggests an involvement of the tyrosine kinase pathway in the regulation of ATP-binding cassette protein (ABC-transport protein) mediated multidrug resistance in cancer cells. The aim of this study was to examine whether EGFR inhibition sensitizes HCCs to chemotherapy and to elucidate its mechanism.
Gesehen am 29.07.2022